Mea culpa : lessons on law and regret from U.S. history - Bender, Steven (New York University Press, 2015)
In Mea Culpa, Steven W. Bender examines how the United States' collective shame about its past has shaped the evolution of law and behavior. We regret slavery and segregationist Jim Crow laws: we craft our legislation in response to that regret. By examining policies and practices that affected the lives of groups that have been historically marginalized and oppressed, Bender is able to draw persuasive connections between shame and its eventual legal manifestations. Analyzing the United States' historical response to its own atrocities, Bender identifies and develops a definitive moral compass.